Coolie Types, Trinidad - (:unkn) unknown (My University, 2008)
A young East Indian girl in a sitting position, dressed in sari and adorned with traditional Indian jewelry.
Colour: Pink, yellow and gold hues; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Young women--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Jewelry--India